Dead by dawn - Doiron, Paul (Doiron, Paul. Mike Bowditch mysteries., 2021)
"Maine game warden Mike Bowditch finds himself in a life-or-death chase in this new thriller from the bestselling mystery series by Edgar Award nominee Paul Doiron"--